Nursing a canine with presumptive tremorgenic mycotoxicosis following ingestion of mouldy dog food – a case report. Issue 6 (3rd June 2018) - Chapman, Emily
Abstract: A one-year-old neutered female Labrador Retriever presented with twitches and subsequent generalised tonic–clonic seizure activity following ingestion of mouldy dog food. Further complicating factors were hyperthermia and metabolic acidosis. Initial emergency treatment involved seizure management, blood analysis, intravenous fluid therapy, active cooling and decontamination via gastric lavage, administration of activated charcoal and an intralipid infusion. The patient was maintained under general anaesthesia to manage the seizure activity. Post-anaesthetic management included treatment of aspiration pneumonia, physiotherapy, intravenous fluid therapy and management of an indwelling urinary catheter. The patient was discharged 48 h post-admission without further complication.